Study on management of various poisoning cases at a tertiary care teaching hospital - Shanmugam, Sriram; Anu Wilson, Nissy (International Journal of Pharmacology and Toxicology, 2016)
Aim/Objective: The main objective of the study is to assess the management of various poisoning cases and to know the role a clinical pharmacist can play in management and prognosis of poisoning cases.Method: A Retrospective study was carried out for a period of three months to know the various poisoning cases admitted in the intensive care units of a tertiary care teaching hospital. All the data regarding the patient and the management of the case were recorded in a pre-designed patient profile form and were analyzed. The study also focuses on preparing a nomogram for the management of various types of poisoning in the study site. It is also planned to study the co-relation between education status and their implications in prognosis of the poisoning cases.Result: A total of 22 patients of various poisoning cases were studied, out of which 13 intentional (69.23%) and 9 unintentional (40.90%) poisonings were reported. It was seen that adults between the age of 21-30yrs were more prone to suicidal poisoning.Conclusion: The majority of poisoning cases were with the use of drugs for suicidal purpose, in young age group and women. Activities including preventive measures, professional education and public education and also clinical pharmacist intervention/involvement in management of poisoning cases in the hospital by providing poison information is the need of the hour.